Words and deeds : Shaping urban politics from below in late medieval Europe. - Eersels, Ben; Haemers, Jelle, 1980- (2020)
This book sheds light on why, how and when citizens participated in the urban political process in late medieval Europe (c. 1300-1500).0This book focuses on the city and urban politics, because historically towns have been an interesting laboratory for the creation and development of political ideas and practices, as they are also today. The contributions in this volume shed light on why, how and when citizens participated in the urban political process in late medieval Europe (c. 1300-1500). In other words, this book reconsiders the involvement of urban commoners in political matters by studying their claims and wishes, their methods of expression and their discursive and ideological strategies. It shows that, in order to garner support for and establish the parameters of the most important urban policies, medieval urban governments engaged regularly in dialogue with their citizens. While the degree of citizens? active involvement differed from region to region and even from one town to the next, political participation never remained restricted to voting for representatives at set times. This book therefore demonstrates that the making of politics was not the sole prerogative of the government; it was always, to some extent, a bottom-up process as well.
boek
Keywords: 940.19 -- Geschiedenis van Europa:--1270-1492